Інтенсивна вирва у всмоктувальному трубопроводі насоса - Орел, Вадим Ігорович (Національний університет "Львівська політехніка", 2019)
The research of critical pressure during the suction of water by a pump is given.
Intense air funnel in tail pipe (of the pump)